STATE AND TENDENCIES OF PRODUCTION CHARACTERISTICS OF WHEAT AND MAIZE IN SERBIA - Vukelic, Natasa; Novković, Nebojša; Šarac, Veljko (Journal on Processing and Energy in Agriculture, 2022)
The aim of the research is to determine the state and tendencies in the movement of production parameters of wheat and corn in Serbia for the period from 2005-2020. Analyzed parameters are harvested area, yield and total production. Descriptive statistics were used to determine the state and tendencies of the observed features. In order to predict the value of production parameters from 2021 to 2023, two methods were used: ARIMA model and extrapolation of the average rate of change of the analyzed parameters. Since the ARIMA model did not give satisfactory results due to a short time series (16 years), annual rates of change were used to extrapolate the production characteristics for the period 2021-2023. Using extrapolation of the average rate of change, the authors concluded that the yield of corn and wheat in the analyzed period showed a tendency to grow, with the areas of both crops showing a tendency to fall. Total wheat and corn production have tendency to grow. The results of the forecast indicate that the volume of wheat production is expected to be 15.54% higher, and the volume of corn 28.41%, during the prediction period in relation to the multi-year averages of the analyzed period.